LH and hCG Action on the Same Receptor Results in Quantitatively and Qualitatively Different Intracellular Signalling - Casarini, Livio; Lispi, Monica; Longobardi, Salvatore; Milosa, Fabiola; La Marca, Antonio; Tagliasacchi, Daniela; Pignatti, Elisa; Simoni, Manuela (PloS one, 2012)
Human luteinizing hormone (hLH) and chorionic gonadotropin (hCG) act on the same receptor (LHCGR) but it is not known whether they elicit the same cellular and molecular response. This study compares for the first time the activation of cell-signalling pathways and gene expression in response to hLH and hCG. Using recombinant hLH and recombinant hCG we evaluated the kinetics of cAMP production in COS-7 and hGL5 cells permanently expressing LHCGR (COS-7/LHCGR, hGL5/LHCGR), as well as cAMP, ERK1/2, AKT activation and progesterone production in primary human granulosa cells (hGLC). The expression of selected target genes was measured in the presence or absence of ERK- or AKT-pathways inhibitors. In COS-7/LHCGR cells, hCG is 5-fold more potent than hLH (cAMP ED(50): 107.1±14.3 pM and 530.0±51.2 pM, respectively). hLH maximal effect was significantly faster (10 minutes by hLH; 1 hour by hCG). In hGLC continuous exposure to equipotent doses of gonadotropins up to 36 hours revealed that intracellular cAMP production is oscillating and significantly higher by hCG versus hLH. Conversely, phospho-ERK1/2 and -AKT activation was more potent and sustained by hLH versus hCG. ERK1/2 and AKT inhibition removed the inhibitory effect on NRG1 (neuregulin) expression by hLH but not by hCG; ERK1/2 inhibition significantly increased hLH- but not hCG-stimulated CYP19A1 (aromatase) expression. We conclude that: i) hCG is more potent on cAMP production, while hLH is more potent on ERK and AKT activation; ii) hGLC respond to equipotent, constant hLH or hCG stimulation with a fluctuating cAMP production and progressive progesterone secretion; and iii) the expression of hLH and hCG target genes partly involves the activation of different pathways depending on the ligand. Therefore, the LHCGR is able to differentiate the activity of hLH and hCG.